2003
DOI: 10.3168/jds.s0022-0302(03)73750-3
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effect of Transition from Conventional to Automated Milking on Teat Skin and Teat End Condition

Abstract: A higher milking frequency, as a consequence of milking with an automated milking system, incorporates a threat to teat condition. To study the effect of transition from conventional to automated milking on teat skin and teat end condition, 40 lactating Holstein-Friesian cows and heifers from a high yielding dairy herd were randomly allocated to either a conventional or an automated milking system group. In the latter group, automated milking was initiated during the study period, while conventional milking wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Recoding was applied for further analyses (1 = ≤2.5; 2 = 2.5-3.5; 3 = ≥3.5). The teat skin and teat apex condition were determined based on a 9-point scale visual scoring system (De Vliegher et al, 2003) and recoded (0 = without cracks; 1 = with cracks). Quarter milk SCC was determined at the Flanders Milk Control Centre (Lier, Belgium) using a Fossomatic 5000/FC (Foss Electric, Hillerød, Denmark).…”
Section: Short Communicationmentioning
confidence: 99%
“…Recoding was applied for further analyses (1 = ≤2.5; 2 = 2.5-3.5; 3 = ≥3.5). The teat skin and teat apex condition were determined based on a 9-point scale visual scoring system (De Vliegher et al, 2003) and recoded (0 = without cracks; 1 = with cracks). Quarter milk SCC was determined at the Flanders Milk Control Centre (Lier, Belgium) using a Fossomatic 5000/FC (Foss Electric, Hillerød, Denmark).…”
Section: Short Communicationmentioning
confidence: 99%
“…To evaluate the profi tability of implementing IMF during early lactation, one must consider not only milk yield but also potential effects on performance and udder health. For example, over-milking negatively affects teat condition (Hillerton et al, 1990), and De Vliegher et al (2003) suggested that teats of heifers may be especially sensitive to changes in milking frequency. Because heifers have not been previously exposed to milking, they provide a unique opportunity to quantify the effects of IMF on udder health.…”
Section: Effects Of Increased Milking Frequency During Early Lactatiomentioning
confidence: 99%
“…The importance of clean udders and a hygienic milking routine in reducing the risk for intramammary infections is well recognized (Silk et al, 2003;Zecconi et al, 2003). However, the importance of a proper teat conditioning has only recently been recognized (De Vliegher et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Teat tissue and skin are considered the first line of defence against infections and, recently, the importance of preserving teat skin conditions has been recognized as one of the most important factors to reduce the risk of infections (Neijenhuis et al, 2000). In dairy herds, teat skin conditions could be impaired by different factors including weather (Burmeister et al, 1998) and disinfectants for pre-and post-milking teat disinfection (De Vliegher et al, 2003). Therefore, the evaluation of teat skin condition could be useful to assess the risk of mastitis in the dairy herd and to identify the potential risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation